Mechanical and failure behavior of three-dimensional six-directional braided composites bolted joint. (May 2017) - Tang, Yuling; Zhou, Zhengong; Pan, Shidong; Tan, Zhiyong; Wu, Hongwei
Experiments and finite element simulation were used to investigate the influence of geometric parameters on failure response of a single-lap bolted joint. Single- and double-bolt joints in three-dimensional six-directional braided composites were tested. The failure modes and mechanisms of the joints were evaluated. To accurately predict bearing strength, a three-dimensional composite damage model was used, which included the Yamada–Sun failure criteria based on the characteristic curve method. The finite element method (FEM) was validated by experimental results. The geometric reference value and failure envelope for the single-lap bolted joint were obtained. The results showed that the carrying capacity of the single-lap bolted joint decreased and the failure mode also changed owing to the secondary bending. It can also be obtained that increased the number of bolt rows can effectively reduce the secondary bending of the plates and thus generated less severe net tensile stresses.